ENVIRONMENTAL AND LEGAL FRAMEWORK FOR THE REGULATION OF ENERGY RESOURCE UTILIZATION - Khaitov Panji Bukharovich (European Science Publishing, 2025)
In this article, opinions were expressed on the improvement of regulatory documents and their analysis regarding the environmental and legal framework and system for regulating the use of energy resources of Energeia. Also, the most important issues related to the theory of Environmental Law, the further development of the system of environmental and legal foundations for the regulation of the use of energy resources were analyzed. It was studied from the point of view of the problems of issues of Environmental Legal Regulation of the use of energy sources, the national and international significance of energy law in the natural resource system, the origin of the right to use it within the framework of scientific research. The environmental and legal basis for regulating the use of energy resources in the energy sector is carried out in certain forms and methods.
Keywords: Energy conservation, development strategy, renewable energy sources, fuel and energy resources, energy security, thermal energy, law, global environmental issues.